Determinants of Indonesian Nickel Exports: Panel Data Analysis using Gravity Model Approach - Hartono, Billie Ariyanta; Brata, Aloysius Gunadi (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2025)
This research investigates the determinants of Indonesia’s nickel exports to major destinations—China, Japan, the United States, Malaysia, and Singapore—from 2003 to 2022. By employing a gravity model, the study validates its utility in explaining Indonesia’s nickel export patterns. The results indicate a positive relationship between the economic size of importing countries and Indonesia’s nickel exports, while increased geographical distance negatively impacts these exports. The estimation also incorporated control variables such as inflation, real exchange rates, and a COVID-19 dummy. These findings highlight the importance of proactive adaptation to global market dynamics to ensure the continued strength of Indonesia’s nickel export sector.